Achilles tendon shear wave speed tracks the dynamic modulation of standing balance - Acuña, Samuel A. (Physiol Rep, 2019)
Standing balance performance is often characterized by sway, as measured via fluctuations of the center of pressure (COP) under the feet. For example, COP metrics can effectively delineate changes in balance under altered sensory conditions. However, COP is a global metric of whole‐body dynamics and thus does not necessarily lend insight into the underlying musculotendon control. We have previously shown that shear wave tensiometers can track wave speeds in tendon as a surrogate measure of the load transmitted by the muscle‐tendon unit. The purpose of this study was to investigate whether shear wave metrics have sufficient sensitivity to track subtle variations in Achilles tendon loading that correspond with postural sway. Sixteen healthy young adults (26 ± 5 years) stood for 10 s with their eyes open and closed. We simultaneously recorded COP under the feet and shear wave speed in the right Achilles tendon. We found that Achilles tendon shear wave speed closely tracked (r > 0.95) dynamic fluctuations of the COP in the anteroposterior direction. Achilles tendon wave speed fluctuations significantly increased during standing with eyes closed, mirroring increases in COP fluctuations. These results demonstrate that tendon wave speed can track the subtle variations in Achilles tendon loading that modulate COP in standing. Hence, shear wave tensiometry exhibits the sensitivity to investigate the muscular control of quiet standing, and may also be useful for investigating other fine motor and force steadiness tasks.